Post a New Question

math

posted by on .

(5)/(x) - (2)/(x-3) = 0

5(x-3) - 2(x) = x(x-3)
5x-15-2x = x^2 -3x
3x-15 = x^2 -3x

this is where i get stuck please help thanks

  • math - ,

    Let's try it differently.


    5/x = 2/(x-3)
    5x - 15 = 2x
    3x = 15
    X = 5

  • Peter - math - ,

    Peter, anything multiplied by zero is still zero,
    so your second line should have been
    5x-15-2x = 0

    Now you have the same as what MatssRiceBowl has in the method he suggested.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question